OPPORTUNITIES FOR DEVELOPING BOOK INTEREST AMONG SENIOR PRESCHOOL CHILDREN THROUGH DIGITAL TECHNOLOGIES - Askarova A.A.; Akmadi M.A. (Foundations and Trends in Modern Learning, 2025)
This study aims to identify the opportunities for developing book interest among senior preschool children through the use of digital technologies. The research questions address which pedagogical approaches and digital tools are most effective, the role of the teacher in integrating these technologies, and how such tools influence children’s reading motivation. A total of 145 scientific articles from the Scopus database (2005–2025) were examined using the PRISMA methodology, of which 129 were included in the final analysis. The findings highlight the effectiveness of digital resources and multimedia tools in enhancing preschool children’s cognitive curiosity and reading motivation. Specifically, digital stories, animated books, and interactive reading platforms were found to positively influence children’s visual perception, emotional engagement, and motivational interest. The importance of teachers’ digital competence and methodological preparedness was also strongly emphasized. The results of the study demonstrate the significance of integrating information and communication technologies into the educational process within contemporary learning environments. The study provides a scientific basis for effectively using digital resources to foster book interest among children in preschool educational settings and may serve as a theoretical foundation for developing future practical programs